Molecular Detection and Characterization of Leptospira spp. in Rodents from Different Habitats in Mgeta Ecosystem, Morogoro - Tanzania - Mritha, Gladness; Mafie, Eliakunda; Katakweba, Abdul Seleman; Mkupasi, Ernatus; Misinzo, Gerald; Hakizimana, Jean; Massawe, Apia (Universitas Airlangga, 2025)
Background: Leptospirosis, a neglected zoonotic disease caused by Leptospira spp., poses a major public health threat in tropical regions, including Tanzania. Rodents are the principal reservoirs responsible for environmental contamination and disease transmission to humans and domestic animals. However, information on Leptospira infection in rodents inhabiting undisturbed and restored forests in Tanzania remains scarce. Purpose: This study aimed to detect and characterize Leptospira spp., infecting rodents and shrews in the Mgeta ecosystem, Morogoro, Tanzania, to better understand their potential role in maintaining and transmitting the pathogen across habitats. Method: A cross-sectional study was conducted from January to March 2024. Rodents and shrews were live-trapped from undisturbed forests, farms, fallow lands, naturally restored forest corridors, and human dwellings. DNA was extracted from kidney tissues and screened using semi-nested PCR targeting the secY gene. Results: A total of 207 small mammals were captured, consisting of 98.55% rodents and 1.45% shrews. Leptospira spp., were detected in 9 (4.3%) rodents, with Praomys (44.4%), Lophuromys (33.3%), and Mastomys natalensis (22.2%) showing the highest prevalence. Infections were mainly detected in farm, forest, and corridor habitats. Phylogenetic analysis identified all isolates as Leptospira borgpetersenii, exhibiting 98.44–98.99% similarity with strains from Spain, Portugal, South Africa, and the United States. Conclusion: The detection of L. borgpetersenii across multiple habitats highlights its ecological persistence and potential zoonotic risk in the Mgeta ecosystem. Strengthened surveillance and integrated public health strategies are essential to mitigate leptospirosis transmission in agricultural and forest-edge communities.